Precious and Dear to Us is Only This Place: The Transformative Potential of Monumental Remnants - Zachary Bray (Washington University Journal of Law and Policy, 2023)
When monuments are torn down, what remains, and what should we do with the remains? In the United States as elsewhere, recent political and social conflicts have led to the destruction or relocation of many monuments—sometimes spontaneous, sometimes carefully planned. Much attention has been focused on these processes of removal and relocation, and the laws that hinder or advance these changes. On the other hand, relatively little attention has been paid to what remains behind after monuments are removed or destroyed: the vacant spaces, empty pedestals, fragments of statues, and so forth. Sometimes these remnants are protected by laws that failed to protect the original monuments. Oftentimes what is left behind may become a monument in its own right, though it may carry very different messages than the original. This Essay explores some of the legal issues associated with monumental remnants and considers how the law can be used, and misused, to shape the repurposing of these sites.
Keywords: Monument Remnants; Confederate; Monuments; Reclamation; Repurpose